2012
DOI: 10.1007/978-1-62703-194-3_16
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic, Physiological, and Molecular Evaluation of Rice Chilling Stress Response at the Vegetative Stage

Abstract: Rice is a chilling-sensitive plant that is particularly prone to injury during the early stages of seedling development and during flowering. Significant variation exists between subspecies with japonica cultivars generally being less sensitive than most indica cultivars. In most temperate and subtropical countries where rice is grown, crop damage often occurs during the early stages of seedling development due to occasional cold snaps coinciding with the first few weeks after direct seeding in late spring to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Oxidative damage is the primary contributor to cold injuries in plants (de Los Reyes et al, 2013). Therefore, the MDA content and ion leakage were measured as indictors of lipid peroxidation and direct cell damage.…”
Section: Overexpression Of Osaox1a Results In Less Oxidative Damage Umentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative damage is the primary contributor to cold injuries in plants (de Los Reyes et al, 2013). Therefore, the MDA content and ion leakage were measured as indictors of lipid peroxidation and direct cell damage.…”
Section: Overexpression Of Osaox1a Results In Less Oxidative Damage Umentioning
confidence: 99%
“…Cold exposure at the seedling and subsequent vegetative growth stages can lead to poor germination, yellowing leaves, and growth retardation (de Los Reyes et al, 2013). Unpredictable chilling snaps at the reproductive stage causes heading delay and high sterility, resulting in severe yield losses (Jena et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Plants have evolved diverse mechanisms in response to chilling and freezing temperatures (Zhu et al 2007). Although some studies on chilling or cold shock responses have been reported (Chaikam & Karlson 2008;Chawade et al 2013;de Los Reyes et al 2013;Mao & Chen 2012;Yang et al 2013a), the differences between the genetic basis of chilling and cold tolerance were seldom addressed. To the best of our knowledge, this study was the first attempt to address the difference in genetic basis of chilling and cold shock stress tolerance.…”
Section: Distinct Genetic Basis Of Natural Chilling and Cold Shock Tomentioning
confidence: 99%
“…The ecogeographical differentiation of the two subspecies has been reported (Londo et al 2006;Yu et al 2003). It has been generally accepted that japonica rice had higher potential in cold adaptability than indica rice (Cheng et al 2007;de Los Reyes et al 2013;Lu et al 2014;Ma et al 2015;Morsy et al 2005;Pan et al 2015), but the genetic evidence for this is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The procedures of Ballou et al (2007) was adopted to determine the % electrolyte leakage from the L1, L2, and L3 leaf discs by measuring the electrical conductivity (EC) in 2 ml of pure nanopure water (16 to18 M∧) before and after stress using a Fisherbrand TM Traceable TM conductivity meter (Thermo Scientific, Waltham, MA, USA). The %EL from intact tissues was determined relative to total tissue electrolytes after boiling, expressed either %EL or electrolyte leakage index (ELI), according to de los Reyes et al (2012).…”
Section: Methodsmentioning
confidence: 99%